Listeria monocytogenes-associated respiratory infections: a study of 38 consecutive cases. (December 2018) - Morgand, M.; Leclercq, A.; Maury, M.M.; Bracq-Dieye, H.; Thouvenot, P.; Vales, G.; Lecuit, M.; Charlier, C.
Abstract: Objectives: Listeria monocytogenes (Lm) is a foodborne human pathogen responsible for severe infections, including septicaemia, neurolisteriosis, and maternal–foetal and focal infections. Little is known about Lm- associated respiratory tract or lung infections. Methods: We conducted a retrospective study of culture-proven cases of Lm pleural infections and pneumonia reported to the French National Reference Centre for Listeria from January 1993 to August 2016. Results: Thirty-eight consecutive patients with pleural infection (n = 32), pneumonia (n = 5), or both (n = 1) were studied; 71% of these were men. Median age was 72 (range 29–90). Two patients presented with concomitant neurolisteriosis. All patients but one reported at least one immunosuppressive condition (97%), with a median number of 2 (range 0–5), including 29% (8/28) with current exposure to immunosuppressive therapy and 50% (17/34) with ongoing neoplasia; 75% (21/28) reported previous pleural or pulmonary disease. Antibiotic therapy mostly consisted in amoxicillin (72%) associated with aminoglycoside in 32%. Chest-tube drainage was performed in 7/19 patients with empyema (37%); 25% of the patients (7/30) required intensive care management. In-hospital mortality reached 35% and occurred after a median time interval of 4 days (range 1–33 days). Three patients had recurrence of empyema (time interval of 1 week to 4 months after treatment completion). Altogether, only 13/31 patients (42%) diagnosed with Lm respiratory infection experienced an uneventful outcome at 2-year follow-up. Conclusion: Lm is a rare but severe cause of pneumonia and pleural infection in older immunocompromised patients, requiring prompt diagnosis and adequate management and follow-up.